Rectangular module for large scale solar simulator based on high-powered LEDs array - Napat Watjanatepin; Patcharanan Sritanauthaikorn (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
The article describes a large scale of rectangular light source design comprised of six different types of high-power light emitting diodes (LEDs). The new modular based on the LED solar simulator with the greatest size using the symmetrical LED positioning method. The experiment provided the irradiation of the solar simulator in the class AAA over 416 cm2. The rectangular LED module illustrated the uniform distribution of the irradiance across the sample plane area. It reached the class A of air mass 1.5 for global spectrum (AM1.5G) (1000 W/m2) covering the 400 nm to 1100 nm wavelength range. The proposed system offered a spectral match of 100%, the temporal instability equivalent to 0.611%, and a non-uniformity of irradiance less than 2%. When the proposed solar simulator was tested in solar cell characteristics under standard test conditions, it was found that the short circuit current error between the sample solar cell under our solar simulator and the standard solar simulator was less than 0.538%. This proposed design is, therefore, an interesting design that can be applied easily and economically further for large scale solar simulators with its modular system.